Evaluasi Sistem Informasi Manajemen Rumah Sakit Di RSUD Indrasari Kabupaten Indragiri Hulu Riau - johan, dwiyumelia; Hartono, Budi (Komunika : Jurnal Ilmiah Komunikasi, 2023)
Indrasari Rengat Regional General Hospital (RSUD) is a referral health service facility belonging to the Indragiri Hulu Regency Government. Initially, Indrasari Rengat Hospital was called RSUD Rengat and was located in Rengat District, which was founded in 1965. From the results of observations, it was found that there were still several obstacles in the operation of this hospital management information system, such as slow operation of the system and poor internet connection. Information system evaluation is also a real effort to find out the actual state of information system implementation. The HOT fit analysis model positions the key components of an information system: people, organization, technology, and benefits. The aim of this research is to find out how to evaluate the hospital management information system (SIMRS) using the HOT Fit methodology. The research method uses a literature review. The research results explain that there are three factors that influence the net benefit of SIMRS at Indrasari Rengat Regional Hospital, namely user satisfaction, organizational structure, and regulations. Meanwhile, factors that do not influence the net benefit of SIMRS RSUD Indrasari Rengat are the level of system utilization, environmental organization, system quality, information quality, service quality, and leadership. The conclusion is to carry out SIMRS assessments regularly, not only during certification or when problems occur, because assessing the system and users will reduce the severity of problems/limitations.